Predisposing Factors Affecting the Compliance of Pregnant Women in the Third Trimester in Carrying Out Antenatal Visits: Faktor Predisposisi yang Mempengaruhi Kepatuhan Ibu Hamil Trimester III dalam Melaksanakan Kunjungan Antenatal - Pani, Widya; Usman, Hastuti; Sumiaty, Sumiaty; Narmin, Narmin; Hadina, Hadina; Djaba, Azzahra Fitri (Napande: Jurnal Bidan, 2024)
Background: Mamboro Health Center is one of the health centers that experience problems in antenatal care visit compliance, in 2023 the coverage of K4 as many as 350 people (97.2%) has decreased compared to 2022. Objective: To identify predisposing factors that affect pregnant women's compliance in the third trimester with antenatal visits. Methods: Quantitative research method, with a cross-sectional design using 50 samples of pregnant women in the third trimester at the Mamboro Health Center. Samples were taken on a total sampling basis. Univariate and Bivariate data analysis using the chi-square test. Results: Univariate data were obtained from mothers who were obedient in carrying out antenatal visits, 56% of whom were The results of the Chi-Square test showed a relationship between ANC Visit compliance with age (p-value 0.0027), education (p-value 0.005), occupation (p-value 0.000) and no relationship with parity (p-value 0.052). Conclusion: Age, Education and Employment are related to antenatal visits and Parity is not related. It is recommended that the Mamboro Health Center provide counseling programs more often on the importance of regular antenatal visits during pregnancy.